Nutritional support of cats and dogs with renal disease. Issue 9 (2nd September 2017) - Collins, Sarah
Abstract: It is widely accepted that nutrition plays an important role in supporting cats and dogs with renal disease, and it is proven to increase longevity when a specifically formulated renal diet is fed. Adapted levels of nutrients such as phosphorus, protein and calcium are important to assess when selecting an appropriate diet, and the hydration status of the patient and how to keep on top of water intake must be considered alongside this. Not only is the choice of diet important, but also the palatability as well as when and how the diet is introduced and fed.